Extreme polygyny results in intersex differences in age-dependent survival of a highly dimorphic marine mammal. Issue 3 (22nd March 2023) - Volzke, Sophia; Cleeland, Jaimie B.; Hindell, Mark A.; Corney, Stuart P.; Wotherspoon, Simon J.; McMahon, Clive R.
Abstract : Developmental differences in vital rates are especially profound in polygamous mating systems. Southern elephant seals ( Mirounga leonina ) are highly dimorphic and extremely polygynous marine mammals. A demographic model, supported by long-term capture–mark–recapture records, investigated the influence of sex and age on survival in this species. The study revealed clear differences between female and male age-dependent survival rates. Overall juvenile survival estimates were stable around 80–85% for both sexes. However, male survival estimates were 5–10% lower than females in the same age classes until 8 years of age. At this point, male survival decreased rapidly to 50% ± 10% while female estimates remained constant at 80% ± 5%. Different energetic requirements could underpin intersex differences in adult survival. However, the species' strong sexual dimorphism diverges during early juvenile development when sex-specific survival rates were less distinct. Maximizing growth is especially advantageous for males, with size being a major determinant of breeding probability. Maturing males may employ a high-risk high-reward foraging strategy to compensate for extensive sexual selection pressures and sex-specific energetic needs. Our findings suggest sex-specific adult survival is a result of in situ ecological interactions and evolutionary specialization associated with being a highly polygynous marine predator.